(untitled) (Revista Tópos, 2013)
O estudo de arqueologia nas áreas dos Sítios Arqueológicos Itatiba e Itatiba II tiveram por objetivo a obtenção de informações sobre os processos culturais, abrangendo as populações indígenas e as frentes pioneiras da sociedade brasileira, evidenciadas na cultura material contida nos registros arqueológicos, incorporando-os à memória regional e nacional e evitando as perdas dessas informações. O presente artigo tem como objetivo apresentar os resultados da pesquisa arqueológica realizada com o grés, a cerâmica vidrada e o vidro dos Sítios Itatiba e Itatiba II. Palavras-chave: sítio arqueológico histórico, patrimônio cultural, cerâmica histórica, lítico. THE STONEWARE, THE CERAMIC GLASS AND GLASSES OF HISTORIC SITES ITATIBA AND ITATIBA II Abstract: The study of archaeology in the areas of the Archaeological Sites Itatiba and Itatiba II has aimed to collect information on cultural processes, comprehending the Indian population and the pioneer groups of the Brazilian society shown by the cultural material contained in the archaeological records, and also incorporating them into the regional and national memories, in order to avoid the loss of such information. The current article aims to present the results of the archaeological research carried on with the grès, the glassy pottery and glasses of the Sites Itatiba and Itatiba II. Key words: historical archaeological site, cultural heritage, historic pottery, lithic.